Studi Komparatif Uji Metode Penyuluhan terhadap Peningkatan Pengetahuan Petani - Iskandar, Iskandar (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
This research to know comparison demonstration method and talk method to increase knowledge about processing straw rice as organic fertilizer at rice plants. This research to implemented in Konda sud district and Konawe district, with involve 30 person farmer. they to distribute in two groups with selective Simple Random Sampling. Treatment to research an experiment with a test at the experiment group. The result of the research indicates that treatment demonstration method and talk method could to increase farmer knowledge into processing straw rice as organic fertilizer at rice plants. An analysis effectiveness method to indicate talk method 52,80 % and demonstration method 70 %, this date to indicate demonstration method more effective than talk method, with the result that demonstration method effective to using by communicator in diffusion and adoption technology and to increase farmer.